Pablo Neruda: A compromised poet - Vidal Costa, Adriane (Pontificia Universidad Javeriana, 2014)
This article intends to understand the roots of the compromise of the Chilean poet Pablo Neruda. To do so, we analyze its politic behavior and its speech in the context of its relation with the communism, the antifascism, The Civil War in Spain and the Soviet Union. We reflect on its taking of position in favor of the communism, the revolution and its relation with the communist politic culture, considering its contradictions and changes of opinion.Lastly, we emphasize how the poetic word, in Neruda’s case, served as an instrument of combat and politic action.